Ponte para o devir: um trajeto por entre saberes discursivos - Vargas, Rejane Maria Arce (2008)
In our research, we propose a reflection about subjectivation process in what it concerns the notion of resistance related to discourse in the Nova Santa Marta community, in Santa Maria, RS, a farm occupied in 1991 by a group of families organized by Movimento Nacional de Luta pela Moradia. The corpus comprises texts of students of Escola Marista Santa Marta, the first educational institution to be set in the occupancy; pictures of the community taken by the students; interviews with the local leader of the social movement and an institutional video of the school. These texts, organized around the discourse of social mobilization, were analyzed in order to bring to light the historicity of this discourse by observing its functioning and the way it circulates. Our focus is the designation bridge , recurrence strongly highlighted in a group of texts, analyzed as a symptom of something else . Above all, our interest was the way of thinking about the language according to the political implications which are present on the linguistic materiality, bringing key concepts of Discourse Analysis of French-Brazilian orientation, which are linked to the movements of the subjects and discourses in face of social urgencies. Thus, the analytical hearing we have done permitted us to (re)think the concepts of discursive formation, class struggle and resistance, in the emergency of fluid identities face to weakness of the State as a totalitarian center, showing that the resistance is not a vector of the discourse which can happen to instate singularities in a speedy time and space, but which claims for a significant intervention of linked metaphors in behalf of new subjective strategies.